2020
DOI: 10.21203/rs.3.rs-27313/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring structurally diverse plant secondary metabolites as a potential source of drug targeting different molecular mechanisms of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) pathogenesis: An in silico approach

Abstract: Plants are endowed with a large pool of structurally diverse small molecules known as secondary metabolites. Present study aims to virtually screen these plant secondary metabolites (PMS) for their possible anti-SARS-CoV-2 properties targeting four protein/enzymes which determines viral pathogenesis. Results of molecular docking and data analysis revealed a unique pattern of structurally similar PSM interacting with the target protein. Among the top-ranked PSM with lower binding energy, >50% were triterpeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Through molecular-docking studies, Khalifa et al (2020) found that some hydrolysable tannins, in particular pedunculagin, tercatain, and castalin, might serve as potential inhibitors of SARS-CoV-2 as they were able to specifically bind the 3CL protease catalytic site. In parallel studies, Hariprasad et al (2020) tested the virtual interaction between many plant secondary metabolites and four target proteins involved in COVID-19, the host protease TMPRSS2 and the three virus proteins, Spike, main protease, and RNA-dependent RNA polymerase, and predicted among the class of triterpenoids the most active compounds in blocking the Spike-binding site. Bhatia et al (2020) also identified PC among dietary polyphenols as a potential inhibitor of Spike and other viral proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Through molecular-docking studies, Khalifa et al (2020) found that some hydrolysable tannins, in particular pedunculagin, tercatain, and castalin, might serve as potential inhibitors of SARS-CoV-2 as they were able to specifically bind the 3CL protease catalytic site. In parallel studies, Hariprasad et al (2020) tested the virtual interaction between many plant secondary metabolites and four target proteins involved in COVID-19, the host protease TMPRSS2 and the three virus proteins, Spike, main protease, and RNA-dependent RNA polymerase, and predicted among the class of triterpenoids the most active compounds in blocking the Spike-binding site. Bhatia et al (2020) also identified PC among dietary polyphenols as a potential inhibitor of Spike and other viral proteases.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel studies Hariprasad et al 2020 tested the virtual interaction between many plant secondary metabolites and four target proteins involved in Covid-19, the host protease TMPRSS2 and the three virus proteins, Spike, Main Protease and RNA-dependent RNA polymerase, and predicted among the class of triterpenoids the most active compounds in blocking the Spike binding site 61 . Bhatia et al 37 (2020) also identified PC among dietary polyphenols as potential inhibitor of Spike and other viral proteases.…”
Section: Discussionmentioning
confidence: 99%